Identification of Candidate Variants Associated With Bone Weight Using Whole Genome Sequence in Beef Cattle - Niu, Qunhao; Zhang, Tianliu; Xu, Ling; Wang, Tianzhen; Wang, Zezhao; Zhu, Bo; Gao, Xue; Chen, Yan; Zhang, Lupei; Gao, Huijiang; Li, Junya; Xu, Lingyang (Frontiers in Genetics, 2021)
Bone weight is critical to affect body conformation and stature in cattle. In this study, we conducted a genome wide association study for bone weight in Chinese Simmental beef cattle based on the imputed sequence variants. We identified 364 variants associated with bone weight, while 350 out of them were not included in Illumina BovineHD SNP array, and several candidate genes and GO terms were captured to be associated with bone weight. Remarkably, we identified four potential variants in a candidate region on BTA6 using the Bayesian fine-mapping. Several important candidate genes were captured including LAP3, MED28, NCAPG, LCORL, SLIT2 and IBSP, which have been previously reported to be associated with carcass traits, body measurements and growth traits. Notably, we found that the transcription factors related to MED28 and LCORL showed high conservation across multiple species. Our findings provide some valuable information for understanding the body stature in beef cattle.